Lipids with long chain polyenoic fatty acids (PUFA) of the n-9 series in rat epididymal cells - Luquez, Jessica Mariela (2010)
In rats, epididymal sperm maturation is associated with the acquisition of glycerophospholipids (GPL) with uncommon C20- C24 carbon PUFA of the n-9 series, particularly 22:4n-9-rich plasmenylcholine. Little is known about how the epididymal epithelium participates in this accretion. In this study, three epididymal regions (caput, corpus, cauda) were isolated for lipid and fatty acid analysis. Unexpectedly, the main n-9 PUFA-rich epididymal GPL including plasmalogens were those of ethanolamine rather than those of choline. Epididymal triacylglycerols (TAG) were highly enriched in 18:1n-9, a precursor of 22:4n-9, whereas the ether-linked triglycerides (ADG), as the GPL, were rich in C20-C24 n-9 PUFA (mainly 22:4n-9). The epididymal n-9 PUFA-rich ADG were made up by important proportions of 1-O-alkyl and 1-alk-1´enyl diacylglycerols. This contrasts with the ADG of testis, where the former subclass predominates over the latter and both are rich in 22:5n-6. Although 22:4n-9-rich GPL and ADG were present in the three epididymal segments, they were significantly more concentrated in the corpus, the metabolically most active region of the epididymis. Our results suggest an active involvement of epididymal cells in the lipid remodeling undergone by spermatozoa during their maturation, most of which takes place before the mature gametes are stored in the cauda region.